If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11m + 1 = -10m + 18 Reorder the terms: 1 + -11m = -10m + 18 Reorder the terms: 1 + -11m = 18 + -10m Solving 1 + -11m = 18 + -10m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '10m' to each side of the equation. 1 + -11m + 10m = 18 + -10m + 10m Combine like terms: -11m + 10m = -1m 1 + -1m = 18 + -10m + 10m Combine like terms: -10m + 10m = 0 1 + -1m = 18 + 0 1 + -1m = 18 Add '-1' to each side of the equation. 1 + -1 + -1m = 18 + -1 Combine like terms: 1 + -1 = 0 0 + -1m = 18 + -1 -1m = 18 + -1 Combine like terms: 18 + -1 = 17 -1m = 17 Divide each side by '-1'. m = -17 Simplifying m = -17
| 8(7n-4)=-144 | | 8-n=3(2n-4) | | -11m+1=-10+18 | | -1/2(8x+2)+1/5(35x+10) | | 4b-7=20+4b | | (4u-5)(3+u)=0 | | 6b^2+23=11 | | 40/4=5x+2(-4x) | | 5/4(x+2)=3 | | 5w+41=3(w+9) | | 0.333333(x+3)+0.1666666(x-6)=x+3 | | (4x+1500)-(2x+1800)=0 | | -4/3x^2-19/18x-19/36=0 | | 2y+3=3(7+7) | | G+2(3+g)=4(g+1) | | 2=400/x | | (x+5y)dy=-(2x+3y)dx | | 7=5(x+5)-7x | | onethird(x+3)+onesixth(x-6)=x+3 | | 5xa-7a^2=2a^2+2ax | | -6x-3(7x-26)=-111 | | 4a-2a+11=6a-13 | | 9w+5= | | 5ax-7a^2=2a^2+2ax | | 8(-7+8v)=200 | | 9w-5= | | 1p-15=13-6p | | 10p+6=-18-2p | | 29=4x-5 | | 2x^2=-2 | | -9v-6+7v=16 | | (2x+1500)-(4x-1800)=0 |